Cold-induced genetic instability in micropropagated Pistacia lentiscus L. plantlets - Koc, Ibrahim; Akdemir, Hulya; Onay, Ahmet; Ciftci, Yelda Ozden (Springer Heidelberg, 2014)
Genetic stability of plants during in vitro propagation and conservation is one of the important aspects of plant biotechnology. In the present study, micropropagated P. lentiscus L. shoot cultures, which are cultivated for the mastic resin, have been cold stored up to 12 months at 4 A degrees C in the dark for different durations (2, 4, 6, 8, 10 and 12 months) and genetic alterations in cold storage conditions were evaluated. Growth parameters such as proliferation rate, shoot numbers per explant, shoot lengths and shoot forming capacity were also calculated. Since the highest proliferation rate (100 %) was obtained in 6 month-stored shoot cultures without any severe influence of cold stress on proliferation ability, amplified fragment length polymorphism (AFLP) and inter-retrotransposon amplified polymorphism (IRAP) marker systems were used to determine genetic stability in the plantlets after this storage period. Totally, 702 scorable bands were produced by 10 AFLP primer pairs. Genetic similarity value of the non-stored (control) plant and cold-stored clones ranged from 0.66 to 0.84 with a mean of 0.74. In the case of IRAP, 159 bands were produced by 8 IRAP primers. Genetic similarity value of the non-stored plant and cold-stored clones varied from 0.65 to 0.83 and the average genetic similarity value was determined as 0.72. The genetic similarity indices revealed that genetic variability was similar in both techniques. Our results showed that tissue culture and especially cold storage of P. lentiscus L. may result transposons activation, thus could cause genetic instability.
Keywords: Pistacia lentiscus L.; Cold stress; Retrotransposon; IRAP; AFLP